IMPLEMENTASI PROGRAM PENANGGULANGAN KEMISKINAN DI PERKOTAAN (P2KP) BERBASIS LINTAS AGAMA - Suyanto Suyanto (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to identify and analyze forms of implementation of interfaith-based urban poverty reduction programs (P2KP), to identify and analyze the level of responsiveness in implementing poverty reduction program policies, to identify and analyze the level of community acceptance of poverty reduction program policies, and to determine and analyze the factors that influence the implementation of poverty reduction program policies in urban areas. The research method used is descriptive qualitative research. Descriptive method through a qualitative approach that aims to understand poverty alleviation in urban areas with research objects such as behavior, perception, motivation and carrying out other actions. The results of this study indicate that the forms of implementation of poverty reduction program policies in urban areas have been carried out according to the P2KP policy stages, government responsiveness in implementing poverty reduction program policies, the community accepts and supports poverty reduction programs, and communication factors, resources, attitude of implementers, and bureaucratic structure are factors that influence the successful implementation of P2KP policies. In cross-religious, especially Islam, in overcoming poverty we as Muslims have an obligation to raise the dignity of the poor. This is mentioned in the Qur'an surah al-Maa'uun verses 1-3 which means